AB1039 Better Outcomes of Disease Activity in A Large Cohort of Rheumatoid Arthritis Patients Treated under Treat To Target Recommendations. (15th July 2016) - Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; Palacio, N.; Castro, C.; et al.
Abstract : Background: Treat to Target (T2T) strategy becomes from the need to develop therapeutic targets and tools to achieve defined outcomes in rheumatoid arthritis (RA). This strategy is being used last years in Colombia. On the other hand a multidisciplinary care team (MCT) model was generated in order to improve outcomes. Objectives: The aim of this study was to describe global change in Disease Activity Score 28 (DAS28) using T2T strategy for a 24-month period in a large cohort of patients from a Colombian specialized in RA center with a MCT model. Methods: A descriptive retrospective study was performed. Records of patients from specialized in RA center were reviewed; those patients were followed-up under T2T standards. Clinical follow-up was designed by the authors according to DAS28 as follows: every 3–5 weeks (DAS28 >5.1), every 7–9 weeks (DAS28 ≥3.1 and ≤5.1), and every 11–13 weeks (DAS28 <3.1). Therapy had to be adjusted with DAS28 >3.2 unless patient's conditions don't permit it. A MCT model means that a patient should be seen by other specialties such as physiatrist, physical and occupational therapy, nutritionist and psychologist at least 3 times a year. We divided patients in three groups: low disease activity (LDA), moderate disease activity (MDA) and severe disease activity (SDA) patients and the aim of the study was to look at what percentage of patients who were in moderate or severe disease activity reached a low disease activity or remission (REM). Descriptive epidemiology was done, percentages and averages were calculated; the median of each variable was analyzed using t-Student assuming normality for DAS28 distribution and the level activity disease was analyzed using Pearson's statistics. Results: 1147 patients were included in this study, 934 (81%) women and 213 (19%) men. Mean was 62±10 years. In regard to treatment it was found that 370 (33%) patients were treated with biologics, and 767 (67%) patients with conventional therapy. It was found a global increase in the percentage of patients in LDA/REM and decrease in moderate and severe disease activity groups. The mean of DAS28 was 4.1±1.1 at the beginning and 24 months after was 2.8±0.61. At 24 months was observed an increase in percentage of patients in remission or LDA (up to 80%) and a decrease in percentage of patients in MDA/SDA disease activity statistically significant. The difference of medians for each variable showed improvement with statistical significance (p<0.00). Although there was a slight decrease in HAQ, this was not statistically significant. Conclusions: This study shows improvement of DAS28 and level of disease activity in a cohort of RA patients from a specialized center in Colombia treated under recommendations of T2T strategy and based on a MCT model. This revision shows the importance of T2T follow-up and treatment for this disease. Disclosure of Interest: None declared